POLA DAN KARAKTERISTIK PERMUKIMAN MASYARAKAT SUKU DAYAK MUALANG DI DESA EMPAJAK, KECAMATAN BELITANG HILIR, KABUPATEN SEKADAU - Febriani, Fransiska; Nurhamsyah, Muhammad; Khaliesh, Hamdil (Program Studi Arsitektur Fakultas Teknik Universitas Tanjungpura, 2025)
This study aims to understand the settlement patterns and characteristics of the Dayak Mualang community in Empajak Village, Belitang Hilir District, Sekadau Regency, and to analyze the cultural and livelihood factors that influence it. By understanding these settlement patterns, the characteristics of the Dayak Mualang settlements in the area can also be revealed in more depth. Therefore, the study of the patterns and characteristics of the Dayak Mualang settlements is a crucial way to see the specific values of Empajak Village, which contains cultural richness and customary orders that have shaped the unique characteristics of the Dayak Mualang community. The background of the problem shows that the formation of settlements is strongly influenced by cultural aspects, including customary norms, history, livelihood systems, and social structures. However, in the era of globalization, the identity and locality of indigenous settlements are vulnerable to change. This study uses a qualitative approach with a rationalistic approach. Data analysis is carried out interactively through data reduction, data presentation, and drawing conclusions. The results show that the Dayak Mualang settlement pattern in Empajak Village tends to be clustered or linear, strongly influenced by the tradition of communal life, the concept of Temawang Tampun Juah (ancestral inheritance land managed together), and dependence on water sources and land for farming and gardening activities. The settlement's characteristics are characterized by the presence of the Betang House as a communal and spiritual center, the use of local materials, and a spatial layout that reflects kinship and mutual cooperation activities. Despite facing external influences, the Dayak Mualang community demonstrates selective adaptation and efforts to revitalize traditions to maintain their settlement identity. This research is expected to contribute to the understanding of traditional architecture and settlements, as well as serve as a basis for efforts to preserve local culture.